A simple HPLC–MS/MS method for the determination of polymyxin B in human plasma and its application in the pharmacokinetic study in elderly patients infected with multidrug-resistant Gram-negative bacteria - Hu, Sheng; Guo, Nan; Zeng, Juan; Li, Yue; Zhang, Yahui; Jiang, Jinjiao; Leng, Bing; Shen, Chengwu (Frontiers in Pharmacology, 2024)
Introduction: Polymyxin B is widely used to treat infections caused by multidrug-resistant Gram-negative bacteria. However, the pharmacokinetic study data of PB in the elderly are scarce. Herein, a simple method to measure the concentration of PB in human plasma was developed and validated by high performance liquid chromatography—tandem mass spectrometry, and it was applied to a PK study in the elderly. Methods: PB was extracted from human plasma by a rapid protein-precipitation method using 0.1% formic acid in methanol and then separated on an ultimate AQ-C18 column using linear gradient elution with a 0.5-mL/min flow rate. Subsequently, PB was detected using a mass spectrometer operated in positive-ion and multiple-reaction-monitoring modes. Results: The lower limits of quantification of the method for Polymyxin B1 and Polymyxin B2 were 1.00 and 0.10 μg/mL, respectively. The linear ranges for PB1 and PB2 were 1.00–20.02 and 0.10–2.04 μg/mL, respectively. Patients receiving a 75-mg maintenance dose every 12h had AUCss, 24 h, and Css, av values of 117.70 ± 37.03 μg h/mL and 4.14 ± 1.74 μg/mL, respectively. For patients receiving a 100 mg maintenance dose, these values were 152.73 ± 70.09 μg h/mL and 5.43 ± 2.85 μg/mL, respectively. Conclusion: The validated HPLC–MS/MS method was successfully applied to a study on the pharmacokinetics of PB in elderly patients infected with multidrug-resistant Gram-negative bacteria. Both two dose strategies in this study would have a excessive PB exposure in the elderly patients then the therapeutic window recommended by guidelines.